744 The incidence of physical contacts in youth ice hockey associated with body checking experience. (1st September 2016) - Janzen, Leticia; Martinez, German; Krolikowski, Maciek; Romanow, Nicole; Palacios-Derflingher, Luz; Nadeau, Luc; Emery, Carolyn
Abstract : Background: Hockey Canada's 2013 body checking (BC) policy change was informed by evidence that BC leads to a >3-fold increased risk of injury compared with non-BC leagues. Video analyses found a reduction in high intensity physical contacts (PC) following this policy change. The association between BC experience and incidence of PCs has not been examined. As such, the incidence of intensity and types of PC were examined following the policy change in Pee Wee (PW) leagues (ages 11–12) with (Calgary) and without (Québec) BC experience. Methods: PW games were videotaped in Calgary (N = 21, with BC experience) and Québec City (N = 20, without BC experience), both non-BC leagues. Games were analysed using Dartfish with a validated observation system to quantify incidence of PC. Five levels of intensity (trunk contacts coded Level 1–5 intensity) and other types of PC (limb/head/stick). PC incidence rates per team-game and incidence rate ratios (IRR) (95% CI) were estimated to compare games between two cohorts. Results: In total 4433 trunk contacts in Calgary and 2667 in Québec were recorded. Of the trunk contacts, 97.5% (Calgary) and 95.7% (Québec) were classified as low level PC. The incidence of total trunk contacts (number of contacts per team-game) was higher in Calgary than Québec (IRR = 1.58, 95% CI: 1.40–1.79). There was no difference in high intensity contacts (Level 4 [IRR = 0.72 95% CI: 0.48–1.07], Level 5 [IRR = 1.21, 95% CI: 0.57–2.56]). The incidence of other PCs was lower in Calgary than Québec (IRR = 0.71, 95% CI: 0.53–0.96). Conclusion: Following a policy change disallowing BC, PW players with experience BC had a greater incidence of total trunk contacts but not greater high intensity contacts than players without BC experience. Players with no experience had a higher incidence of other PCs. These results inform a greater understanding of mechanisms of contact in youth ice hockey that will in turn inform injury prevention and player development.